Pengembangan Alat Peraga Mikrohidro Berbasis CTL Untuk Meningkatkan Pemahaman Konsep Pada Materi Fluida Dinamis - Syafira, Ayuni Nisa; Medriati, Rosane; Hamdani, Dedy (UNIVERSITAS INDRAPRASTA PGRI, 2024)
This study is the development of a microhydro demonstration tool based on contextual teaching and learning aimed at testing the feasibility of the media, understanding the responses of students and teachers to the media, and determining the level of students' understanding of dynamic fluid material in grade XI at SMAN 11 Kota Bengkulu. The method used in this study is R&D using the ADDIE model. Research instruments include expert validation sheets, questionnaires for student and teacher responses, as well as pre-tests and post-tests. The expert validation results show final percentages by three validators of 82.89%, 92.1%, and 93.4%, with an average percentage of 89.47%, interpreted as highly feasible. The results of student and teacher response questionnaires show a percentage of 95.11%, interpreted as highly feasible. Furthermore, the improvement in students' conceptual understanding, measured by N-gain at 0.73, falls into the criteria of high improvement in students' understanding of dynamic fluid material. Therefore, the CTL-based microhydro demonstration tool is considered suitable for improving students' conceptual understanding of dynamic fluid material.